Characterization of the thermally transferred optically stimulated luminescence (TT-OSL) of BeO. (July 2019) - Yukihara, E.G.
Abstract: The objective of this work was to characterize more in depth the newly discovered thermally transferred optically stimulated luminescence (TT-OSL) of BeO. The studies include a more detailed investigation of the pre-heating temperature and time required to induce the TT-OSL signal; the reproducibility, additivity, and stability of the TT-OSL signal at room temperature and under ambient light exposure; the TT-OSL response to high doses (up to 25 Gy); and the possible recuperation of the OSL signal at room temperature. The results indicate that the TT-OSL is maximum for a pre-heating to 260 °C, if a heating rate of 5 °C/s is used. The TT-OSL decreases with readouts (pre-heating plus OSL readout), indicating depletion of the source of trapped charges. Sensitivity changes are observed in both OSL and TT-OSL signals to the same extend. Furthermore, it was demonstrated that the TT-OSL is additive: the TT-OSL is proportional to the total dose delivered to the detector, whereas the OSL signal is proportional to the dose since the last bleaching. This relationship holds up to ∼5 Gy; above this dose, the TT-OSL starts to saturate. The kinetics of the TT-OSL signal with pre-heating temperature and duration is consistent with a simplified model in which charges from an optically insensitive (or "difficult to bleach") trap are transferred to an optically sensitive trap, both having similar thermal stabilities with a difference in activation energy of the order of 0.1 eV. The TT-OSL signal is stable in the dark up to the maximum duration investigated here (50 days), decaying slowly under exposure to ambient light. Furthermore, we report evidence of recuperation of the OSL signal at room temperature, which may be caused by a similar process as the one responsible for the TT-OSL signal. The results have obvious implications for practical dosimetry using BeO, including the possibility of re-estimating the doses if the detectors are accidently exposed to light, the possibility to check if the detectors have been exposed to light, the potential recuperation of OSL signal at room temperature and its influence on dosimetry if the detectors have been exposed to high doses, or the potential to use the shape of the OSL curve or the ratio between the OSL and TT-OSL signals for linear energy transfer estimation in ion beam dosimetry. Highlights: Thermally transferred optically stimulated luminescence (TT-OSL) of BeO was characterized. Sensitivity changes are observed in both OSL and TT-OSL signals to the same extend. It was demonstrated that the TT-OSL is additive and proportional to the total dose delivered. Kinetics of the TT-OSL signal is consistent with a charge transfer between traps. TT-OSL signal is stable in the dark up to the maximum duration investigated here (50 days).